Bibliometric analysis of global research on psychological well-being, subjective burden, and psychosocial support of family caregivers of cancer patients - Waleed M Sweileh (Health Psychology Open)
This study delves into the realm of informal cancer caregivers. Through a meticulous bibliometric analysis, the study sheds light on the burgeoning interest in this field, with a significant focus on the psychological well-being, subjective burden, and psychosocial support for caregivers. A significant portion of the retrieved articles ( n = 1366) was published after 2017 and primarily disseminated through a select number of journals. Notably, the study reveals a substantial gap in randomized controlled trials addressing interventions tailored to family caregivers, indicating a critical need for more high-quality trials to guide effective support strategies. Despite the increasing recognition of caregivers’ significance, limited research collaboration was observed, emphasizing the importance of fostering collaborative efforts to address cultural differences and expand the scope of research on cancer caregivers globally. The findings underscore the urgent call for comprehensive interventions and collaborative endeavors to optimize the well-being of family caregivers.